A review of the Madagascan species of the genus Cestradoretus Ohaus (Coleoptera: Scarabaeidae: Rutelinae: Adoretini) - Frolov, Andrey V.; Montreuil, Olivier (Zootaxa, 2019)
The genus Cestradoretus Ohaus, 1912 was erected by Ohaus (1912) to accommodate a Madagascan Adoretini species, C. tenuirostris Ohaus, 1912. This genus is characterized by the adults having the apex of the labrum with a long, fine, acute process curved downwards. In the addition to the above mentioned paper, Ohaus (1912) also described C. acomys Ohaus, 1912 from Tanzania, and later moved Adoretus tarsatus Klug, 1855, described from Mozambique, to Cestradoretus (Ohaus 1916).  Later, Machatschke (1965) described two species from Africa, C. freyi Machatschke, 1965 from Botswana and C. minusculus Machatschke, 1965 from Somalia, and Frey (1976) described C. clypealis Frey, 1976 from Somalia. Thus, Cestradoretus included six species, one from Madagascar and five from Africa.